The role of digital device use on the risk of migraine: a univariable and multivariable Mendelian randomization study - He, Zongqing; Qiu, Fan; Yang, Jing; Zhao, Min (Frontiers in Neurology, 2024)
The pervasive integration of digital devices into daily life has raised concerns about their potential health impacts. This study aimed to explore the causal relationships between digital device use and the risk of migraine using Mendelian randomization (MR).Methods: Genetic data on digital device use and migraines were sourced from large-scale genomewide association studies conducted by UK Biobank, FinnGen Study and the International Headache Genetics Consortium. Univariable MR (UVMR), meta-analysis, and multivariable MR (MVMR) approaches were conducted to explore and verify the causal effects of digital device use (including mobile phone use, computer use, playing computer games, and watching television) on migraine risk. Sensitivity analyses were conducted using Cochran's Q, MR-Egger intercept test, MR pleiotropy residual sum and outlier, MR Radial, MR Steiger and leave-one-out-methods.Results: UVMR analyses revealed that genetically predicted mobile phone use was significantly associated with an increased risk of overall migraine (odds ratio [OR] = 2.39, P = 9.78e-5) and migraine without aura (MO) (OR = 2.25, P = 0.024). Additionally, there were significant positive associations between genetically predicted television watching and the risk of overall migraine (OR = 1.63, P = 2.12e-5) and MO (OR = 2.10, P = 4.98e-5). These results were further supported by the meta-analysis and MVMR analysis. Sensitivity analysis indicated no heterogeneity or pleiotropy.This comprehensive MR study provides preliminary evidence for the causal impact of mobile phone use and television watching on the risk of migraines. Further studies are needed to explore these associations across different populations.